Changes

Jump to navigation Jump to search
36 bytes added ,  02:02, 22 September 2015
Line 523: Line 523:  
  H(x) = \left\{
 
  H(x) = \left\{
 
         \begin{array}{l}
 
         \begin{array}{l}
         R \; x \le 0\\
+
         R \qquad x \le 0\\
         R - (R - r) x \; 0 < x < 1\\
+
         R - (R - r) x \qquad 0 < x < 1\\
         r \; x > 1
+
         r \qquad x > 1
 
         \end{array}         
 
         \end{array}         
 
         \right.\\
 
         \right.\\
Line 542: Line 542:  
   H(x) = \left\{
 
   H(x) = \left\{
 
         \begin{array}{l}
 
         \begin{array}{l}
         R \; x \le 0\\
+
         R \qquad x \le 0\\
         R - (R - r) x \; 0 < x < 1\\
+
         R - (R - r) x \qquad 0 < x < 1\\
         r \; x > 1
+
         r \qquad x > 1
 
         \end{array}         
 
         \end{array}         
 
         \right.\\
 
         \right.\\
Line 565: Line 565:  
H'(x) = \left\{
 
H'(x) = \left\{
 
         \begin{array}{l}
 
         \begin{array}{l}
         0 \; x \le 0\\
+
         0 \qquad x \le 0\\
         - (R - r) \; 0 < x < 1\\
+
         - (R - r) \qquad 0 < x < 1\\
         0 \; x > 1
+
         0 \qquad x > 1
 
         \end{array}         
 
         \end{array}         
 
         \right.
 
         \right.
 
</math>
 
</math>
349

edits

Navigation menu